Pengaruh Inflasi, Kurs, Suku Bunga, dan Harga Minyak Dunia Terhadap Indeks Harga Saham Industri Pertambangan di Bursa Efek Indonesia Periode 2012-2015 - Yulia Istia Ningsih; Muthmainnah Muthmainnah (Universitas Batanghari Jambi, 2019)
This study aims to determine how the influence of inflation, exchange rates, interest rates, and world oil prices on the mining industry stock price index in the period 2012-2015. The object in the 2012-2015 research period is mining companies on the Indonesia Stock Exchange. The population used in this study were 31 mining companies and was based on a purposive sampling method which produced a sample of 11 companies. The dependent variable is represented by the mining industry stock price index, while the independent variables in this study are inflation, exchange rates, interest rates, and world oil prices. Partially the results of this study indicate that during the 2012-2015 period the variable exchange rates and world oil prices affected the mining industry's stock price index, while inflation and interest rates did not affect the stock price index mining industry. Simultaneously shows the influence of independent variables on the mining industry stock price index.